Determination of the size of synthesized zinc oxide nanoparticles using the Scherrer equation - Osorio Anaya, Ana María (2023)
The purpose of this study was to determine the size of zinc oxide nanoparticles (NPs-ZnO) synthesized by the chemical precipitation method from the precipitation reaction between zinc acetate and sodium hydroxide. Then, characterization was made by X-ray diffraction (XRD). The characterization results obtained by this instrumental method correspond to the zincite structure (ZnO) of the hexagonal system, whose crystalline structural data is registered in the ICDD file PDF 01-075-0576. The determination of the size of NPs-ZnO was performed using the Scherrer equation with data obtained from the diffraction data of the most important planes of the crystal structure of the synthesized nanoparticles. The size of the crystallites determined was approximately 21 nm. This method of determining the size of nanoparticles is not very exact, however, in laboratories that do not have electron microscopy equipment it is useful to obtain approximations of the size of the synthesized nanoparticles.